The Impact of Hyperosmolality on Activation and Differentiation of B Lymphoid Cells - Cvetkovic, Ljiljana; Perisic, Stojan; Titze, Jens; Jäck, Hans-Martin; Schuh, Wolfgang (Frontiers in Immunology, 2019)
B lymphocytes, as a central part of adaptive immune responses, have the ability to fight almost unlimited numbers of pathogens. Impairment of B cell development, activation and differentiation to antibody secreting plasma cells can lead to malignancy, allergy, autoimmunity and immunodeficiency. However, the impact of environmental factors, such as hyperosmolality or osmotic stress caused by differences in salt concentrations in different lymphoid organs, on these processes is not well understood. Here, we report that B cells respond to osmotic stress in a biphasic manner. Initially, increased osmolality boosted B cell activation and differentiation as shown by an untimely downregulation of Pax5 as well as upregulation of TACI and CD138. However, in the second phase, we observed an increase in cell death and less differentiated cells. Osmotic stress resulted in impaired class switch to IgG1, inhibition of phosphorylation of p38 mitogen-activated kinase and a delayed NFAT5 response. Overall, these findings demonstrate the importance of microenvironmental hyperosmolality and osmotic stress for B cell activation.